Analisis Literasi Keuangan dan Dampaknya terhadap Kesejahteraan Rumah Tangga Petani Sayuran - Ayu Kartini Parawansa; Aslam, Annisa Paramaswary (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
This study aims to analyze the level of financial literacy and examine its influence on the household welfare of vegetable farmers. Agricultural households, particularly smallholder vegetable farmers, frequently experience economic vulnerability due to several structural challenges such as unstable agricultural income, seasonal production patterns, fluctuating market prices, limited access to formal financial services, and inadequate financial management skills. These conditions often make farm households more susceptible to economic shocks, including crop failure, input price increases, or sudden market price declines. In this context, financial literacy becomes an essential capability that enables farmers to manage their financial resources more effectively.This research employed a quantitative research design using a survey approach. The study involved 120 vegetable farmers selected as respondents from major vegetable-producing areas. Data were collected through structured questionnaires designed to measure farmers’ financial literacy levels and household welfare conditions. Financial literacy was assessed through indicators such as financial knowledge, financial behavior, and financial attitudes, while household welfare was evaluated based on indicators including consumption stability, education and health expenditures, savings capacity, and overall economic resilience. The collected data were analyzed using descriptive statistics to describe the characteristics and financial literacy levels of respondents, and multiple linear regression analysis to examine the relationship between financial literacy and household welfare.The results of this study highlight the importance of strengthening financial education programs targeted at agricultural communities. Improving financial literacy among vegetable farmers can contribute not only to better household financial management but also to broader rural economic development. Therefore, financial education initiatives should be integrated into agricultural extension programs, farmer group activities, and local government development strategies. Such initiatives may include training in household financial planning, simple bookkeeping for farm businesses, savings management, and responsible credit use. By enhancing farmers’ financial capabilities, these programs can help improve household welfare, strengthen rural economic resilience, and support the long-term sustainability of the agricultural sector.